Direct synthesis of oxygenates via partial oxidation of methane in the presence of O2 and H2 over a combination of Fe-ZSM-5 and Pd supported on an acid-functionalized porous polymer - Kang, Jongkyu; Puthiaraj, Pillaiyar; Ahn, Wha seung; Park, Eun Duck (Applied Catalysis A: General, 2020)
Aqueous-phase partial oxidation of methane over a combination of heterogeneous Fe-ZSM-5 and Pd catalysts was demonstrated in the presence of O2 and H2. Fe-ZSM-5 catalyst active for partial oxidation of methane with H2O2 was prepared by an ion-exchange method. For comparison, homogeneous Fe species (FeSO4) were also used as a catalyst for partial oxidation of methane. Several supported Pd catalysts for the direct synthesis of hydrogen peroxide from H2 and O2 were prepared using activated carbon (AC), AC treated with sulfuric acid (s-AC), as-synthesized hyper-crosslinked porous polymer (HCPP), HCPP with carboxylic group (c−HCPP), and HCPP with carboxylic and sulfonic groups (c-s−HCPP). Among them, the Pd catalyst supported on c-s−HCPP was effective for generating H2O2 in situ, which enabled methane oxidation over Fe-ZSM-5 without any leaching.
Keywords: Carboxylic group; Direct synthesis; Fe-ZSM-5 catalysts; Ion-exchange methods; Methane oxidation; Partial oxidation of methane; Porous polymers; Supported Pd catalysts; Heterogeneous catalysis; Hydrogen peroxide; Liquid-phase oxidation; Methane activation; Methane oxygenates